Who negotiates for a nation? Catalan mobilization and nationhood before the Spanish democratic transition, 1970–1975. Issue 4 (6th June 2016) - Greer, Scott L.
Abstract : Much of the literature on democratic transitions and ethnic conflict focuses on the role of elites, whether as constructive contributors to ethnic harmony and pacted transitions, or as fomenters of disharmony. What these accounts often fail to take into account is the extent to which the existence of political elites is a variable in itself, particularly when their power bases are not organizations like an army but rather nations or classes. The article develops an analysis of how competition for scarce militants and the demands of organizing them shapes the power and importance of elites. It does this through a case study of Catalonia in the years preceding the Spanish transition. During those years Catalonia, both a stateless nation and a potentially divided society, was the site of organizing from the left and right that nearly monopolized militants and channelled their activity into autonomist, inclusive forms of nationalist mobilization that stifled attempts at internal polarization while creating elites who could negotiate on Catalonia's behalf in the transition. In other words, the ability of moderate Catalan nationalists to organize before the transition explains their ability to represent Catalonia and control its fissures later, and contributes to explaining the success of Catalonia as a case of peaceful multinational coexistence.